Desulphurization of diesel fuel using carbon-based metal oxide nanocomposites - Cherubala, Rusumba Bienvenu (Vaal University of Technology, 2021)
This thesis presents a slight on desulphurization process of the commercial diesel fuel using the carbon-based metal oxide nanocomposites such as graphene oxide, ZnO, rGO as a nano-adsorbent, activated carbon (PAC and AC) and charcoal Granular active carbon (GAC) to produce a fuel of less than 10 ppm sulphur content. Due to the high percentage of sulphur compounds in the fuel causing air pollution, acid rain and other problems related to combustion process. The synthesised of sorbents were achieved using incipient impregnation, microwaved-assisted and chemical exfoliation methods. The materials were characterized using Thermogrametric Analyzer (TGA), Fourier transform infrared spectroscopy (FTIR) and X-ray diffractometer (XRD), Brunauer, Emmett and Teller (BET). The examination effect of operating conditions on the adsorption capacity with DBT and Sulphur compounds adsorption, the isotherms and the adsorption kinetic models were evaluated. The experimental data for PAC and AC were well suited to Freundlich isotherm and pseudo second-order kinetic models. The results shown that the sulphur feed concentration, the space velocity and the functional groups of the adsorbents have a considerable effect on the adsorption. In addition, it was observed that the temperature in the range of 30 to 80oC has a significant effect on the adsorption of Sulphur compounds from diesel fuel using 20 wt.% of sorbents. The rGO substrate which contained abundant oxygen functional groups was confirmed to promote the dispersion metal oxide and increased the adsorption efficiency of sulphur compounds (H2S and SO2) by providing oxygen ions weakly bound to the sulphur molecules. For the desulfurization process by adsorption, PAC and AC exhibited a better affinity for 80% removal of sulphur compared to the GAC and GO. The effects of metal species such as zinc oxide (ZnO) and reduced graphite oxide (rGO) composite on the adsorption capacity of hydrogen sulphide (H2S) were investigated. It was found that depending on the copper load, the adsorption capacity of H2S increased up to 20 times compared to pure ZnO. To study the oxidation changes on copper and zinc oxides, crystallite analysis by XRD and chemical state analysis by XPS were performed.
M. Tech. (Department of Chemical Engineering, Faculty of Engineering and Technology), Vaal University of Technology.
Keywords: Desulphurization of diesel fuel; Carbon-based metal oxide; Nanocomposites; Cranular active carbon; Sulphur compounds; Dissertations, Academic -- South Africa.; Nanocomposites (Materials); Petroleum -- Refining -- Desulfurization.